2008
DOI: 10.1073/pnas.0712169105
|View full text |Cite
|
Sign up to set email alerts
|

Helical domain and kinase domain mutations in p110α of phosphatidylinositol 3-kinase induce gain of function by different mechanisms

Abstract: The phosphatidylinositol 3-kinase (PI3K) signaling pathway is upregulated in cancer. PIK3CA, the gene coding for the catalytic subunit p110␣ of PI3K, is mutated in Ϸ30% of tumors of the prostate, breast, cervix, and endometrium. The most prominent of these mutants, represented by single amino acid substitutions in the helical or kinase domain, show a gain of enzymatic function, activate AKT signaling, and induce oncogenic transformation. We have carried out a genetic and biochemical analysis of these hot-spot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
353
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(392 citation statements)
references
References 43 publications
33
353
0
3
Order By: Relevance
“…In contrast, mutations in the helical domain (exon 9) cluster on an exposed surface patch of the protein and may change its ability to interact with other regulatory proteins, which may be different for each tissue. [31][32][33] As expected, analyses of the PTEN mutations revealed that these alterations are more common in pure endometrioid adenocarcinomas compared with that in non-endometrioid adenocarcinomas and mixed tumors. Different studies of colorectal and breast carcinomas have claimed that the PIK3CA and PTEN mutations are mutually exclusive and suggest that carcinogenic signaling through this pathway occurs either through the activation of PIK3CA or inactivation of PTEN.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, mutations in the helical domain (exon 9) cluster on an exposed surface patch of the protein and may change its ability to interact with other regulatory proteins, which may be different for each tissue. [31][32][33] As expected, analyses of the PTEN mutations revealed that these alterations are more common in pure endometrioid adenocarcinomas compared with that in non-endometrioid adenocarcinomas and mixed tumors. Different studies of colorectal and breast carcinomas have claimed that the PIK3CA and PTEN mutations are mutually exclusive and suggest that carcinogenic signaling through this pathway occurs either through the activation of PIK3CA or inactivation of PTEN.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, the kinase domain mutant H1047R acts independently of RAS-GTP binding, but requires p85 for activation. The helical and kinase domain double mutants synergistically activate downstream signaling events and increase cellular transformation, further demonstrating that the individual (helical and kinase domain) mutants operate by different mechanisms (Zhao and Vogt, 2008). All told, the recurrent genetic activation of PI3K is another way in which the PTEN pathway can be disturbed in cancer.…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 97%
“…Furthermore, the helical and kinase domain mutants both have increased kinase activity, but are activated by different mechanisms. Studies performed in chicken embryonic fibroblasts demonstrate that the helical domain mutations (E542K and E545K) require interaction with RAS-GTP, but not with p85 (Zhao and Vogt, 2008). In essence, the helical mutants appear to position the kinase in a way such that it is no longer subject to the negative regulation by p85, but the catalytic domain still requires Ras for activation.…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Considering its important role in cell survival and proliferation, K-ras has been extensively studied in recent years. Previous studies revealed that K-ras gene mutations cause excessive activation of K-RAS/ RAF/MEK/ERK and PI3K/AKT/mTOR signaling pathways [4][5][6][7][8][9].…”
mentioning
confidence: 99%